2018
DOI: 10.1142/s0192415x18500039
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1Receptor Antagonists Facilitate Electroacupuncture Analgesia

Abstract: This study investigated the influence of the histamine H receptor antagonists, chlorpheniramine (CHL) and pyrilamine, on the analgesic effects of acupuncture in mice. Nociceptive response was evaluated by the acetic acid-induced abdominal writhe test. Electroacupuncture (EA) at bilateral ST36 reduced the manifestations of acetic acid-induced abdominal writhing, whereas needle insertion without electrostimulation had no such effect. Notably, EA treatment was not associated with any analgesic effects in mice pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Immunofluorescence confocal microscopy was performed according to the method described by Lin et al (2016, 2018), with some modifications 23 , 33 . Tissue samples from C5-C8 spinal segments were blocked by PBS containing donkey serum 0.5% BSA and 0.4% Triton X-100 before being treated with Iba1 (1:500, #ab5076; Abcam) antibodies for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence confocal microscopy was performed according to the method described by Lin et al (2016, 2018), with some modifications 23 , 33 . Tissue samples from C5-C8 spinal segments were blocked by PBS containing donkey serum 0.5% BSA and 0.4% Triton X-100 before being treated with Iba1 (1:500, #ab5076; Abcam) antibodies for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that chlorpheniramine monotherapy administered at 0.6 mg/kg fails to modulate pain, but when administered with EA, effectively facilitates EA analgesia in mice. 26 It has been suggested that H 1 receptor antagonist therapy may directly or indirectly facilitate opioid binding to opioid receptors, 33 interact with substance P, 34 and have antiserotonergic and/or antiadrenergic effects, 35 all of which are associated with pain modulation. Thus, antihistamine administration may mediate the pain modulation system and act in synergy with EA to facilitate its analgesic effects.…”
Section: Discussionmentioning
confidence: 99%
“…As a pilot trial, the sample size was determined by matching the numbers of study participants to the numbers of animals in our previous study. 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture is widely used to alleviate visceral pain in China, owing to its ability to provide pain relief with few side effects such as addictiveness [ 33 , 34 ]. Several clinical studies have demonstrated the efficacy of acupuncture-moxibustion in visceral pain treatment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%